Society, ethics, and the law: a reader - Mackey, David A. (Jones & Bartlett Learning, 2020)
"Society, Ethics, and the Law: Text Reader is designed for the criminal justice ethics course, typically taught within the criminal justice, philosophy, or social science department. This course is primarily taken by junior and senior undergraduate students who are majoring in criminal justice or other related fields. Ethics is one of the six required topic areas in criminal justice education as defined by the Academy of Criminal Justice Sciences. The Academy of Criminal Justice Sciences standards are located at www.acjs.org/page/ProgramStandards. The required content areas are defined in B.5. Table 1. Although ACJS has moved away from 'certifying' academic programs, the standards still serve as the primary benchmarks for program reviews for criminal justice degree programs. The text consists of 12 sections with five readings per section. Each section consists of an Introduction to the section, three articles related to the topic, and a 'character in context' article. The character in context article is intended to be written by a practitioner with work experience connected to the theme of the section with a more conversational format (versus the articles which are traditional academic articles). This title is contributed by experts in the field, many of whom are prominent within ACJS and have been presenting their topics at relevant conferences to full audiences. The shorter, article format is designed to appeal to today's student, while providing a sufficient depth of coverage as expected by the course instructor. The selected articles range from traditional philosophical based academic articles to conversational style narratives of practitioners' experiences with ethic issues within the criminal justice system. The text will contain topics not traditionally covered in a criminal justice ethics course; this renders the book appealing to ethics courses offered in philosophy and social science departments, while also remaining relevant to criminal justice students"--